2014
DOI: 10.1038/npp.2014.18
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of Cerebral Dopamine D3 Receptors in Alcoholism

Abstract: Animal studies support the role of the dopamine D3 receptor (DRD3) in alcohol reinforcement or liking. Sustained voluntary alcohol drinking in rats has been associated with an upregulation of striatal DRD3 gene expression and selective blockade of DRD3 reduces ethanol preference, consumption, and cue-induced reinstatement. In vivo measurement of DRD3 in the living human brain has not been possible until recently owing to a lack of suitable tools. In this study, DRD3 status was assessed for the first time in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 70 publications
(104 reference statements)
7
59
1
Order By: Relevance
“…Further work has investigated a selective D 3 -antagonist medication in an operant food self-administration paradigm and showed that a D 3 -antagonist attenuated lever presses and food intake in both lean and OB rats, providing preliminary evidence of D 3 R-related motivation to consume food (Thanos et al, 2008). This notion is consistent with clinical data implicating the D 3 R in populations abusing substances that influence nigrostriatal reward pathway function (Boileau et al, 2012;Erritzoe et al, 2014;Matuskey et al, 2014;Payer et al, 2014).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Further work has investigated a selective D 3 -antagonist medication in an operant food self-administration paradigm and showed that a D 3 -antagonist attenuated lever presses and food intake in both lean and OB rats, providing preliminary evidence of D 3 R-related motivation to consume food (Thanos et al, 2008). This notion is consistent with clinical data implicating the D 3 R in populations abusing substances that influence nigrostriatal reward pathway function (Boileau et al, 2012;Erritzoe et al, 2014;Matuskey et al, 2014;Payer et al, 2014).…”
Section: Introductionsupporting
confidence: 69%
“…Our data suggest that D 2/3 Rs are higher in OB compared with NW individuals in regions densely populated with D 3 Rs, thus implicating the D 3 R as a potential pharmacologic target for the treatment of obesity. These data also implicate the same nigrostriatal pathway alterations in obesity that have been previously observed with [ 11 C](+)PHNO in cocaine (Matuskey et al, 2014;Payer et al, 2014), methamphetamine (Boileau et al, 2012), and alcohol (Erritzoe et al, 2014) abusers, indicating excessive food consumption might alter reward pathways in similar ways as do substances of abuse. The direct role of the D 3 R in addiction is not currently clear .…”
Section: Discussionsupporting
confidence: 54%
“…In a second study in primarily cocaine-abusing individuals (Payer et al, 2013), our group replicated the evidence for heightened [ 11 C]-(+ )-PHNO binding in substantia nigra ( + 24% higher binding) in cocaine dependence, a finding that was simultaneously reported by Matuskey et al (2014), who demonstrated that cocaine addiction was associated with an upregulation of D 3 receptors in the substantia nigra ( + 29%), as well as the hypothalamus (+ 28%) and amygdala ( + 35%) (Matuskey et al, 2014). Erritzoe et al (2014) have recently extended the finding of potential D 3 upregulation to alcohol use disorder (n= 16 males), reporting 17% greater [ 11 C]-( +)-PHNO binding in the hypothalamus (where D 3 fraction represents 100%). Further, conducting the study under conditions of blockade with the D 3 -selective antagonist compound GSK598809 (60 mg p.o.)…”
Section: Development Of a Pet Probe To Investigate D 3 Receptors In Hsupporting
confidence: 81%
“…Furthermore, these regions are small and hard to define, and thus potentially sensitive to motion artefact and image misalignment. In areas of mixed D 3 /D 2 binding, it is possible to theoretically estimate the D 3 fraction based on published literature (Tziortzi et al, 2011), but selective pharmacologic blockade is necessary to adequately dissect and estimate the D 3 contribution (see for example Erritzoe et al, 2014). The globus pallidus presents another regional limitation, as it is hard to define on typical T1 and proton density magnetic resonance images because of low contrast due to the numerous striato-pallidonigral myelinated axons that traverse it.…”
Section: Development Of a Pet Probe To Investigate D 3 Receptors In Hmentioning
confidence: 98%
“…In contrast, a recent body of work suggests that, unlike other measured dopaminergic markers, the D 3 receptor might be upregulated in animal models (Le Foll et al, 2005;Neisewander et al, 2004) and in postmortem (Mash, 1997;Staley and Mash, 1996) and living brain of humans with stimulant (Boileau et al, 2012;Matuskey et al, 2014;Payer et al, 2014) and perhaps alcohol (Erritzoe et al, 2014) addiction (see (Boileau et al, 2015b) for a review). General interest in D 3 receptor has developed in large part because of preferential expression of D 3 in limbic brain areas associated with reward/motivation (eg, ventral striatum) and because animal models suggested that D 3 -selective antagonists decrease drug-seeking behavior.…”
Section: Introductionmentioning
confidence: 99%